2008
DOI: 10.4142/jvs.2008.9.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the xenograft bone plate-screw system in lumbar transpedicular stabilization of dogs: anin-vitrostudy

Abstract: We performed biomechanical comparison of a xenograft bone plate-screw (XBPS) system for achieving cadaveric lumbar transpedicular stabilization (TS) in dogs. Twenty dogs' cadaveric L2-4 lumbar specimens were harvested and their muscles were removed, but the discs and ligaments were left intact. These specimens were separated to four groups: the L2-4 intact group as control (group I, n = 5), the L3 laminectomy and bilateral facetectomy group (LBF) (group II, n = 5), the LBF plus TS with metal plate-screw group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…[ 1 ] Therefore, to evaluate and reveal the fusion rate, between the vertebral segments, a considerable amount of experimental studies were reported. [ 4 7 8 9 10 12 13 14 ] Here, biomechanical and histological results of the study show the contributing role of XBPS in lumbar segments of the dogs with TS for stabilization.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…[ 1 ] Therefore, to evaluate and reveal the fusion rate, between the vertebral segments, a considerable amount of experimental studies were reported. [ 4 7 8 9 10 12 13 14 ] Here, biomechanical and histological results of the study show the contributing role of XBPS in lumbar segments of the dogs with TS for stabilization.…”
Section: Discussionmentioning
confidence: 62%
“…The XBPSs were machined (Yunan Machine Tool Works, China) from cadaveric cattle tibia and sized as in the previous study. [ 10 ] Metal screws and plates had same size as in XBPS [ Figure 1 ]. Sterilization of the all equipment was made in autoclave, but XBPSs were boiled in 3% acide borique solution at 15 min for sterilization as described previously.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations